2015
DOI: 10.1016/j.cmi.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between GII.3 norovirus infections and blood group antigens in young children in Tunisia

Abstract: Noroviruses (NoVs) constitute a major cause of gastroenteritis in Tunisia. One hundred and fourteen matched saliva and stool samples were collected from children (n = 114) suffering from acute gastroenteritis at the hospital of Monastir during the winter season 2011-2012. For 98 of 114 children, blood samples were collected for secretor genotyping. NoVs were associated with 36.8% (n = 42/114) of the gastroenteritis cases. The GII.3 genotype was the most common (69% of all NoVs). For patients who were phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 41 publications
7
22
1
Order By: Relevance
“…Other non-GII.4 genotypes were also detected in our study, including GII.1 (1/65, 1.5%), GII.6 (3/65, 4.6%), GII.7 (1/65, 1.5%), GII.13 (2/65, 3%), GII.17 (5/65, 7.7%), and GII.21 (1/65, 1.5%). These non-GII.4 genotypes were previously reported in the MENA region in Lebanon [45], Tunisia [62], Libya [35], Egypt [40], and Turkey [63]. Further genotypes GI.1, and GI.3, GII.1, GII.6, GII.7, GII.13, GII.17, and GII.21 were detected only once throughout the study.…”
Section: Discussionsupporting
confidence: 70%
“…Other non-GII.4 genotypes were also detected in our study, including GII.1 (1/65, 1.5%), GII.6 (3/65, 4.6%), GII.7 (1/65, 1.5%), GII.13 (2/65, 3%), GII.17 (5/65, 7.7%), and GII.21 (1/65, 1.5%). These non-GII.4 genotypes were previously reported in the MENA region in Lebanon [45], Tunisia [62], Libya [35], Egypt [40], and Turkey [63]. Further genotypes GI.1, and GI.3, GII.1, GII.6, GII.7, GII.13, GII.17, and GII.21 were detected only once throughout the study.…”
Section: Discussionsupporting
confidence: 70%
“…The largest number of studies was reported from Turkey ( n = 8), followed by Iran ( n = 6) and Tunisia ( n = 5). The reported NoV infection rates in MENA countries ranged between 0.82% as reported in Morocco [ 33 ] and 36.84% in Tunisia [ 34 ]. When applicable, we calculated the median percentage of NoV infection in individual countries.…”
Section: Resultsmentioning
confidence: 99%
“…In addition GII.3 NoV has been implicated in food-borne outbreaks in both developed and developing countries [ 21 ]. Recent studies show that in several countries, GII.4 is the predominant strain causing diarrhea, followed by GII.3 [ 13 15 ], while in others, GII.3 is the predominant strain [ 22 , 23 ]. These results were derived from studies conducted with children.…”
Section: Discussionmentioning
confidence: 99%